Meet members of the GA4GH executive leadership team (Elsevier, 2021)
In this interview with Cell Genomics, Ewan Birney, Kathryn North, and Heidi Rehm share their vision for the Global Alliance for Genomics and Health (GA4GH). They discuss how the GA4GH is enabling global data sharing to advance genomics and medicine in ways that will ensure equitable participation and benefit for all populations.